A state variable for crumpled thin sheets. Issue 1 (December 2018) - Gottesman, Omer; Andrejevic, Jovana; Rycroft, Chris; Rubinstein, Shmuel
Abstract Despite the apparent ease with which sheets of paper are crumpled and tossed away, crumpling dynamics are often considered a paradigm of complexity. This arises from the infinite number of configurations that disordered, crumpled sheets can take. Here we experimentally show that key aspects of axially confined crumpled Mylar sheets have a very simple description; evolution of damage in crumpling dynamics can largely be described by a single global quantity—the total length of creases. We follow the evolution of the damage network in repetitively crumpled elastoplastic sheets, and show that the dynamics are deterministic, depending only on the instantaneous state of the crease network and not on the crumpling history. We also show that this global quantity captures the crumpling dynamics of a sheet crumpled for the first time. This leads to a remarkable reduction in complexity, allowing a description of a highly disordered system by a single state parameter. A crumpled sheet of paper is a common image in many contexts but crumpling dynamics are considered a complex problem. Using Mylar sheets the authors experimentally show that the evolution of the damage network in crumpling dynamics is largely history independent and the accumulation rate of the total length of all creases can be accurately predicted.